2005
DOI: 10.1029/2004ja010544
|View full text |Cite
|
Sign up to set email alerts
|

Fractal properties of SYM‐H during quiet and active times

Abstract: Detrended fluctuation analysis was applied to the magnetic storm index SYM‐H for the epoch 1981–2002. The objective was to determine the characteristic fractal statistical differences, if any, between a quiet and active magnetosphere. The entire data set comprises over 11 million points that include numerous intervals that can be classified as quiet or active. For quiet intervals we required Kp ≤ 1 for 10,000 consecutive minutes. Similarly, to qualify as an active interval required Kp ≥ 4 for 10,000 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 47 publications
5
73
0
2
Order By: Relevance
“…It is known that the Earth's magnetospheric dynamics is characterized by persistent dynamic correlations (e.g., Dobias and Wanliss, 2009) and near-criticality dynamics (e.g., Consolini, 2002;Wanliss and Uritsky, 2010), which are correlated features in self-organized critical systems in stationary conditions also away from the critical point (Woodard et al, 2007). Furthermore, the persistent character of the magnetospheric dynamics has been shown to undergo dynamical changes during magnetic storms and substorms (e.g., Wanliss, 2005;Balasis et al, 2006;Wanliss and Dobias, 2007). These points suggest that the more complex observed relation between the multifractional nature and the intermittent character of the geomagnetic fluctuations (see, e.g., Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the Earth's magnetospheric dynamics is characterized by persistent dynamic correlations (e.g., Dobias and Wanliss, 2009) and near-criticality dynamics (e.g., Consolini, 2002;Wanliss and Uritsky, 2010), which are correlated features in self-organized critical systems in stationary conditions also away from the critical point (Woodard et al, 2007). Furthermore, the persistent character of the magnetospheric dynamics has been shown to undergo dynamical changes during magnetic storms and substorms (e.g., Wanliss, 2005;Balasis et al, 2006;Wanliss and Dobias, 2007). These points suggest that the more complex observed relation between the multifractional nature and the intermittent character of the geomagnetic fluctuations (see, e.g., Figs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the fractal character of several geomagnetic time series, for example those relative to the geomagnetic indices AE, Dst and SYM-H, changes during magnetic storms and substorms (Uritsky and Pudovkin, 1998;Wanliss, 2005;Balasis et al, 2006;Wanliss and Dobias, 2007;Dobias and Wanliss, 2009). In particular, it has been noticed that the self-similarity properties of these time series change when an intense magnetospheric/geomagnetic activity event approaches.…”
Section: Introductionmentioning
confidence: 99%
“…We also compare the temporal history of these storms as measured by magnetograms and the SYM-H time series. Let us recall that the SYM-H index, measured in nT, is a ground-based magnetic index developed to describe geomagnetic disturbance fields at middle-and low-latitudes with a high-time resolution (Wanliss, 2005a;Wanliss and Showalter, 2006). It is the oneminute high-resolution version of Dst, derived using data from magnetic observatories close enough to the magnetic equator, so as not to be influenced by auroral current systems.…”
Section: An Activity Estimator Based On the Spectral Exponent 2003 Mamentioning
confidence: 99%
“…Some previous works have demonstrated the statistical self-affinity properties observed in the geomagnetic times series (Chang, 1999;Sitnov et al, 2001;Uritsky et al, 2001Uritsky et al, , 2006Kovacs et al, 2001;Lui, 2002;Wanliss, 2005a;Balasis et al, 2006;Wanliss and Dobias, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation